Correction: Peripheral halogenation engineering controls molecular stacking to enable highly efficient organic solar cells. Issue 9 (8th August 2022) - Zou, Yalu; Chen, Hongbin; Bi, Xingqi; Xu, Xiaoyun; Wang, Hebin; Lin, Menglu; Ma, Zaifei; Zhang, Mingtao; Li, Chenxi; Wan, Xiangjian; Long, Guankui; Zhaoyang, Yao; et al.
Abstract : Correction for 'Peripheral halogenation engineering controls molecular stacking to enable highly efficient organic solar cells' by Yalu Zou et al., Energy Environ. Sci., 2022, ; https://doi.org/10.1039/d2ee01340a .